Teachers' attitudes in Ajloun towards fingerprint system - Almomani, Ibrahim Ali Mohammad (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to identify the attitudes of teachers in Ajloun governorate towards the fingerprint system. The study population consisted of (2831) teachers in public schools in Ajloun governorate. The sample of the study was (318) male and female teachers. They were randomized. The study reached a number of results, the most important of which are: Teachers have neutral attitudes towards the fingerprint system, with an arithmetic mean (2.95); Social, job title, job experience, educational qualification, workplace), The study recommended the need to hold courses and workshops to inform teachers of the importance of the fingerprint system, laws and regulations, in addition to flexibility in dealing with teachers in emergency and exceptional circumstances they are going through.
Keywords: teacher trends; fingerprint system